1999
DOI: 10.1016/s0022-5223(99)70329-6
|View full text |Cite
|
Sign up to set email alerts
|

Late results of senning operation

Abstract: Long-term follow-up after the Senning operation shows increasing incidence of sinus node dysfunction and right ventricular dysfunction over time. Deteriorating right ventricular function is a major concern. Its early recognition and initiation of appropriate management to preserve cardiac function is an important follow-up goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 25 publications
3
72
2
1
Order By: Relevance
“…Kirjavainen et al [3] show: 90% of the patients with simple TGA but only 78% of the patients with complex TGA, were alive 15 years after the Senning procedure. These data confirm the finding that the presence of a VSD is a significant risk factor for late death because VSD closure emerged as an independent risk factor for late death in multivariate analysis.…”
Section: Late Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirjavainen et al [3] show: 90% of the patients with simple TGA but only 78% of the patients with complex TGA, were alive 15 years after the Senning procedure. These data confirm the finding that the presence of a VSD is a significant risk factor for late death because VSD closure emerged as an independent risk factor for late death in multivariate analysis.…”
Section: Late Follow-upmentioning
confidence: 99%
“…Survival functional status and quality of life of patients with transposition of the great arteries (TGA), after an atrial switch operation (Senning or Mustard procedure) are reported to be reasonably good after 2 decades of life [1][2][3][4][5][6][7][8]. However, in many cases, It's possible to detect the function of the systemic right ventricle deteriorates, severe tricuspid regurgitation develops or the patients suffer from arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…18 In our series the incidence of late sudden death was 2.9%, which is in agreement with the range of 2-8% reported in the literature. 5,6,[10][11][12][13][14][15][16] …”
Section: Sudden Deathmentioning
confidence: 99%
“…Long-term follow-up after the Senning technique (table II) has shown a better survival when compared with the Mustard technique, ranging from 78 to 90% 10,11,15,16 . It is interesting to note that, in the largest international experience with the Seening technique, Genoni et al 15 report similar mortality rates among patients with associated ventricular and atrial septal defects in Zurich, Switzerland.…”
mentioning
confidence: 99%
“…Complications of the surgery that can be associated with the anatomo-functional conditions of the disease are supraventricular arrhythmias, right ventricular failure, tricuspid regurgitation, and stenosis of either the pulmonary or the systemic venous systems or both of these [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%